Episodic Atlantic Water Inflow Into the Independence Fjord System (Eastern North Greenland) During the Holocene and Last Glacial Period - Van Nieuwenhove, Nicolas; Limoges, Audrey; Nørgaard-Pedersen, Niels; Seidenkrantz, Marit-Solveig; Ribeiro, Sofia (Frontiers in Earth Science, 2020)
Four marine sediment cores from two sites in the Independence Fjord system near the Wandel Sea in eastern North Greenland were analyzed for their dinoflagellate cyst (dinocyst) and foraminiferal fossil content to gain insight into the water mass properties and evolution of the outer fjord system over the Holocene and Last Glacial Period. While regarded as a climate-sensitive region, the climatic history of the area remains largely unknown and has been documented through the study of two composite marine sediment cores only once before. The results presented here reveal that Atlantic waters entered the Independence Fjord episodically during the studied interval. High concentrations of dinocysts and foraminifers in the upper few centimeters of the cores are in line with oceanographic measurements clearly illustrating that Atlantic-sourced waters make up the lower part of the water column in the area in modern times. Radiocarbon dating of foraminiferal tests and increasing microfossil concentrations and diversity towards the top of the cores suggest that this inflow has been occurring for at least 2000 years and intensified towards recent times. The core sections below the upper few centimeters are devoid of (Quaternary) dinocysts and calcareous foraminifera with the exception of the lowermost segments of the longer cores. While low foraminiferal test quantities in these lowermost core sections prevent precise age determination, their radiocarbon ages reveal that they were deposited prior to 30 000 years ago, indicating the existence of a pathway for the occasional intrusion of Atlantic-sourced waters into, and thus relatively small local ice caps around, the fjord system prior to the Last Glacial Maximum. The previously documented early Holocene inflow of Atlantic-sourced waters was not detected in our records, likely suggesting a strong topographical and deglacial control on the routing of these water masses during the early Holocene.